Rural parents' beliefs about healthy eating. (October 2018) - McDonald, Andrea E; Dawkins-Moultin, Lenna; McWhinney, Sharon L
Objectives: This study explored US rural parents' perceived facilitators, challenges and motivators to healthy eating. Methods: Qualitative and purposive sampling was used to recruit one hundred ( N = 100) parents of children enrolled in the fourth grade to participate in a series of focus group sessions. Eligibility criteria included being the head of the household and having a child enrolled in the fourth grade. Parents were questioned about factors impacting everyday lifestyle practices such as nutrition knowledge and eating habits. Data were analysed using grounded theory and constant comparative method. Results: Twelve focus groups sessions were conducted with parents who self-identified as African American (63%), Hispanic (25%) and Caucasian 2%. The majority (52%) of participants indicated they only had some high school education. Healthy eating among parents was highly dependent on socioeconomic status, time, availability and access to foods. Facilitators to healthy eating were school lunch programmes, nutrition education and family preferences. Findings demonstrate that parents tried to eat meals at home, but many factors (fear of genetically modified foods, money and time) prevented healthy eating and food preparation. Parents who consumed or prepared meals at home did so because of family influence and the fear of being unhealthy. Conclusion and implications: This study provides an in-depth understanding of rural parents' efforts to promote healthy eating at home regardless of socioeconomic challenges.